Evaluation of fast disintegrating tablets of Nifedipine prepared by Superdisintegrant addition and sublimation methods (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Fast disintegrating tablets of nifedipine prepared by superdisintegrant addition and sublimation methods were evaluated. Twelve batches of tablets were formulated by direct compression using varying concentrations of crospovidone and croscarmellose sodium. Camphor was incorporated into six of the batches. Their granules were evaluated for pre-compression and post-compression parameters. FTIR analysis of the drug and excipients was also carried out. Results obtained showed that their granules were free flowing with angle of repose < 26° and Carrs index < 19 %. The tablets gave hardness of 3.67-5.99 kgf, friability of < 1 %, wetting and disintegration times of < 101 and < 91 secs, respectively. Dissolution profiles showed all the tablets released over 92 % of their drug within 30 mins. FTIR analysis demonstrated no interactions between nifedipine and excipients. The sublimation method in combination with superdisintegrant addition method of formulation yielded fast disintegrating tablets of superior quality than the superdisintegrant addition method alone. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21901 Dhaka Univ. J. Pharm. Sci. 13(2): 199-205, 2014 (December)